The Difference of Integrin ανβ3 Expression, Leukemia Inhibitory Factors and Superoxide Dismutase Serum Concentration in the Provision of Kebar Extract (Biophytum petersianum Klotczh), Metformin, and Their Combination to Mouse models of Endometriosis - Seindy Glamour; Syarief Thaufik Hidayat; Adi Setyawan Prianto; Widjiati Widjiati (Journal of Biomedicine and Translational Research, 2018)
Background: In endometriosis there is a decrease in endometrial receptivity. Kebar and Metformin grasses are expected to improve the condition of endometrial receptivityObjective: To find out whether there is any effect of giving Kebar grass extract and metformin on endometrial receptivity Methods: The study was designed by using a simple experimental randomization. It was conducted in Obstetrics Gynecology Department - Faculty of Medicine Diponegoro University and Faculty of Veterinary Medicine Airlangga University. Sample calculation was employed. The study was done within five groups including control group with normal mice, group of endometriosis mouse models given placebo, group of endometriosis mouse models given Kebar grass extract, group of endometriosis mouse models given metformin, and group of endometriosis mouse models given the combination of Kebar grass – metformin extract. The examination materials of ανβ3 integrin and Leukemia Inhibitory Factors were taken from the uteri of the mice and measured by the Rammele Scale Index (Immuno Reactive Score), while the Superoxide Dismutase examination using ELISA was derived from mice serum. These examinations were performed by two veterinariansResults: The expression of ανβ3 integrin was significantly higher in the group of mouse models given Kebar grass extract as well as the combination of Kebar and metformin grass extracts (p <0.05) rather than in the group of endometriosis mouse models with no treatment, whereas LIF expression was significantly higher in the group given Kebar grass extract, metformin and combination of both extracts (p <0.05). Serum SOD levels remained the same.Conclusion: The expressions of ανβ3 Integrin and LIF are higher due to the provision of Kebar grass extract as well as the combination of Kebar grass and metformin extracts